Two different trichoscopic patterns of mid-frontal scalp in patients with frontal fibrosing alopecia and clinical features of androgenetic alopecia - Rakowska, Adriana; Waśkiel, Anna; Sikora, Mariusz; Olszewska, Małgorzata; Rudnicka, Lidia (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction . Frontal fibrosing alopecia is a primary lymphocytic cicatricial alopecia with progressive frontotemporal hairline recession. In some cases, hair loss in the mid-frontal scalp, similar to female pattern hair loss, may be observed. Objective. Assessment of the trichoscopic pattern of mid-frontal scalp hair loss in patients diagnosed with frontal fibrosing alopecia. Material and methods. The retrospective analysis included 31 women diagnosed with frontal fibrosing alopecia and hair loss in the mid-frontal scalp and 36 women diagnosed with female pattern hair loss. Results . In patients with frontal fibrosing alopecia two different trichoscopic patterns in the mid-frontal scalp were identified. In 68% of patients (21/31) we observed a diffuse fibrotic pattern. It was characterized by irregular arrangement of follicular units with small areas with loss of follicular units, an increased percentage of follicular units with one hair and a decreased percentage of follicular units with three hairs, normal hair shaft thickness and presence of mild perifollicular scaling. The androgenetic alopecia pattern was present in 32% of patients (10/31). It was characterized by hair shaft thickness diversity (20% or more), a percentage of vellus hairs higher than 10%, presence of yellow dots, an increased percentage of follicular units with one hair and a decreased percentage of follicular units with three hairs. Conclusions. In patients with frontal fibrosing alopecia and coexisting mid-frontal scalp hair loss, we identified two different patterns of this area in trichoscopy: the diffuse fibrotic pattern (more common) and the androgenetic alopecia pattern. This observation may have therapeutic and prognostic implications.